Interrogating incest : feminism, Foucault, and the law - Bell, Vikki, 1967- (Sociology of law and crime., 1993)
Winner of British Sociological Association Philip Abrams Memorial Prize 1993 Within feminism incest has often been subsumed under a discussion of sexual violence and abuse. Yet, important as this is, there has been little account of how feminist work itself relates to other ways of talking about and understanding incest. In Interrogating Incest Vikki Bell focuses on the issue of incest and its place in sociological theory, feminist theory and criminal law. By examining incest from a critical Foucauldian framework she considers how feminist discourse on incest itself fits into existing ways of talking about sex. Closely surveying the historical background to incest legislation and the theoretical issues involve, Vikki Bell delineates their practical implications and shows what uncomfortable questions and important dilemmas are raised by the criminalisation of incest.